Clinical significance of serum bilirubin in primary Sjögren syndrome patients. Issue 3 (6th November 2019) - Zhang, Zunni; Su, Qisheng; Zhang, Liqian; Yang, Zheng; Qiu, Yuling; Mo, Wuning
Abstract: Objective: The purpose of our research was to demonstrate the clinical significance of serum bilirubin in primary Sjögren syndrome patients (pSS). Patients and methods: A total of 116 patients with primary Sjögren syndrome and 138 matched individuals were included in our study. The laboratory parameters of patients with pSS and healthy controls were retrospectively analyzed. Results: Serum total bilirubin, direct bilirubin, and indirect bilirubin were significantly reduced ( P < .001, P = .001, P < .001) while ESR was significantly increased ( P < .001) in patients with pSS when compared with healthy checkup individuals. Statistically, the AUC in patients with pSS is as follows: TBIL = 0.77, P < .001, cutoff value = 7.96; DBIL = 0.617, P = .001 cutoff value = 2.2; and IBIL = 0.786, P < .001 cutoff value = 4.5. Furthermore, our study revealed that TBIL, DBIL, and IBIL were significantly negativity related to ESR ( r = −.406, P < .001; r = −.206, P = .026; r = −.429, P < .001). Interestingly, multiple linear regression analysis showed that when adjusted for sex, age, ALT, and AST, the levels of TBIL, DBIL, and IBIL in patients with pSS were independently correlated with ESR. Conclusions: This study found that the levels of serum bilirubin were reduced and the inflammatory marker was elevated in patients with pSS. Additionally, serum bilirubin was negatively related with ESR and TBIL, DBIL, and IBIL can be used in the clinical diagnosis and follow‐up visits of the patients with pSS.